2013
DOI: 10.1164/rccm.201210-1913oc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Respiratory Microbiome in Healthy Nonsmokers and Smokers

Abstract: Rationale: Results from 16S rDNA-encoding gene sequence-based, culture-independent techniques have led to conflicting conclusions about the composition of the lower respiratory tract microbiome. Objectives: To compare the microbiome of the upper and lower respiratory tract in healthy HIV-uninfected nonsmokers and smokers in a multicenter cohort. Methods: Participants were nonsmokers and smokers without significant comorbidities. Oral washes and bronchoscopic alveolar lavages were collected in a standardized ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

57
664
3
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 672 publications
(751 citation statements)
references
References 26 publications
57
664
3
12
Order By: Relevance
“…Loss of beneficial oral species due to smoking can lead to pathogen colonization and ultimately to disease; this contention is strongly supported by the well-established role of smoking in the onset and progression of periodontitis (Nociti et al, 2015). Previous studies have shown alterations in the abundance of selected oral bacteria in smokers compared with non-smokers (Colman et al, 1976;Ertel et al, 1991;Charlson et al, 2010;Kumar et al, 2011;Hugoson et al, 2012;Morris et al, 2013;Belstrom et al, 2014;Mason et al, 2015); however, results across these studies are largely inconsistent, possibly due to small sample sizes in some, use of different sampling sites in the mouth and use of different laboratory methodologies, some of which impose limitations on bacterial profiling.…”
Section: Introductionmentioning
confidence: 97%
“…Loss of beneficial oral species due to smoking can lead to pathogen colonization and ultimately to disease; this contention is strongly supported by the well-established role of smoking in the onset and progression of periodontitis (Nociti et al, 2015). Previous studies have shown alterations in the abundance of selected oral bacteria in smokers compared with non-smokers (Colman et al, 1976;Ertel et al, 1991;Charlson et al, 2010;Kumar et al, 2011;Hugoson et al, 2012;Morris et al, 2013;Belstrom et al, 2014;Mason et al, 2015); however, results across these studies are largely inconsistent, possibly due to small sample sizes in some, use of different sampling sites in the mouth and use of different laboratory methodologies, some of which impose limitations on bacterial profiling.…”
Section: Introductionmentioning
confidence: 97%
“…One challenging observation is that the lower airway microbiome is more similar to the upper airway microbiome of the same individual than it is to the lung microbiome of a different person (17). Although part of this might be explained if significant carryover had occurred, most data suggest substantial diversity in healthy individuals (7)(8)(9)19). Therefore, it is important to establish the degree of overlap between different individuals.…”
Section: Is There a Core Microbiome?mentioning
confidence: 99%
“…Among various factors, the low culturable bacterial burden in the lung, contamination with upper airway microbiota during sampling, and the difficulties in growing fastidious bacteria have contributed to the presumption that the lung is sterile (3,4). With the use of culture-independent techniques, there is now substantial literature identifying the presence of bacteria products in the lower airways of normal individuals (5)(6)(7)(8). Data from quantitative PCR for 16S ribosomal RNA (rRNA) genes confirm that the bacterial burden in the lower airways is less than in the upper airways.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jusqu'à récemment, les données publiées concernaient essentiellement les microbiomes digestif, cutané, buccal ou génital et leurs liens avec différentes pathologies comme par exemple le diabète. Mais, très récemment, de nombreux microorganismes (bactéries, virus, champignons) ont également été mis en évidence dans les voies aériennes inférieures des sujets en bonne santé, rendant caduque le concept classique de stérilité des voies aériennes normales [1][2][3][4][5]. Plusieurs questions se posent aujourd'hui : ces germes sont-ils des « touristes » ou des résidents permanents du tractus respiratoire ?…”
unclassified